CONSUMER ATTITUDE AND PREFERENCES TOWARDS ORGANIC FOOD PRODUCTS IN CHENNAI CITY - A STUDY - K. Kanchana,; V. Kannan, (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The growing awareness of health, environmental sustainability, and food safety has led to a significant rise in the demand for organic food products globally. Chennai, being a major metropolitan city, has witnessed an increased consumer inclination towards organic consumption. This study aims to analyze consumer attitudes, preferences, and buying behavior regarding organic food products in Chennai. Using a combination of primary and secondary data, the research identifies key factors influencing purchase decisions, including health consciousness, environmental concerns, availability, and price sensitivity. The findings of the study offer valuable insights for marketers, retailers, and policymakers aiming to promote organic consumption in urban areas.